Nivel de conocimiento sobre hipertensión arterial y nivel de autocuidado en adultos del programa de control de enfermería del hospital Essalud II - Tarapoto Abril - Julio 2012 - Pérez Acosta, Yandira Rosario (2012)
This research project entitled: "Level of knowledge about hypertension and level of self-care in adults of the Disease Control Program at the ESSALUD 11 Hospital Tarapoto: April-July 2012" was structured as descriptive correlational of transversal type, having this a quantitative approach, which had as an objective to determine the relationship that exists between the level of knowledge about hypertension and level of self-care of the hypertensive patients. The research project sample population was comprised of 165 patients who met the criteria of the study. In order to collect the relevant data, we used the questionnaire technique and two other instruments: the survey that was designed to determine the level of knowledge about hypertension that the adult patients of the aforementioned program; we also designed a test to determine a level of selfcare. The collected data were systematized using the statistics package by Microsoft Excell 2007 and SPSS 17.0 version. The findings of the study were: 54,5% of hypertensive patients showed an excellent level of knowledge, 32,7% of !he patients showed a good level of knowledge, 7,9% of the patients showed regular knowledge and 4,8% of the patients showed a low level of knowledge. Regarding the level of self-care: 91,5% of the patients had a high level of self care and 8,5% of the patients had a medium level of self-care and by relating both variables X2 c(39.968) < X2 1(7.815) we found that there exists a relationship between a level of knowledge about hypertension and level self-care in hypertensive adults. Therefore, we suggest that it is very important to promote self-care awareness programs that will allow hypertensive patients a better management of their disease.